DINAMIKA SELF-ESTEEM PADA MAHASISWA PENYANDANG TUNADAKSA DI UNIVERSITAS X SURABAYA - Jeanet Yener Hingkua (Universitas Katolik Widya Mandala Surabaya, 2019)
Physical disability is a condition of a physical defect that a person has in which the body part is not functioning properly.This condition makes a person feel negative emotions, and experiences some difficulties in conducting their activities especially because the individual also has a role as a college students. The purpose of this research was to explore self-meaning of individuals with physical disability and how the dynamic process of self-esteem of individuals with disabilities that have a role as college students. Self-Esteem is individuals’ assessment of themselves. Assessments or evaluations made are different between person to person, it can be positive or negative that affects a person's behavior in carrying out their activities and the outcomes.This study used a qualitative-inductive approach with phenomenological methods.The informant in this study were college students with physical disability since birth. Data collection was conducted through interview process with two research informants. The result of this study showed that both informants have a positive judgment to themselves. Both informants were able to accept their physical disabilities that were experienced since childhood and made peace with their less enjoyable experiences in the past. The process of forming positive judgment by the two informants were seen from social support where the two informants had feelings of self-meaning, life values, ability and skills in conducting activities and achieving goals as a child and particularlyas a college student.